TMOD-08. PRIMARY AND RECURRENT GLIOMA PATIENT-DERIVED ORTHOTOPIC XENOGRAFTS (PDOX) REPRESENT RELEVANT PATIENT AVATARS FOR PRECISION MEDICINE - Golebiewska, Anna (Neuro Oncol, 2020)
Patient-derived cancer models are essential tools for studying tumor biology and for preclinical interventions. Although numerous clinical cancer trials are being conducted, many fail due to inappropriate selection of compounds at the preclinical stage. Therefore, better preclinical models are crucial for predicting successful clinical impact. Orthotropic patient-derived xenograft (PDOX) models are of particular importance for brain cancers, as they allow to better recapitulate the brain tumor environment and the blood brain barrier. We created a large collection of PDOXs from primary and recurrent gliomas with and without mutations in IDH1. PDOX models were based on 3D organoids, derived from mechanically minced patient material. Organoids were implanted in the brain of immunodeficient mice and further propagated by serial intracranial transplantations. High grade glioma PDOX models, starting with viable patient-derived organoids, have generally a high tumor take rate, a reproducible phenotype and tumor development time. PDOXs retain histopathological, genetic, epigenetic and transcriptomic features of patient tumors with no mouse-specific clonal evolution. Longitudinal PDOX models confirmed limited evolution of gliomas upon treatment observed in patient tumors. PDOX-derived standardized tumor organoid cultures enabled assessment of drug responses, which were validated in mice. PDOXs showed clinically relevant responses to Temozolomide and to targeted treatments such as EGFR and CDK4/6 inhibitors in (epi)genetically defined groups, according to MGMT promoter and EGFR/CDK status respectively. These data indicate that glioma PDOXs represent clinically relevant avatars for personalized treatment. The use of these models should lead to a more realistic evaluation of the efficacy of novel drugs, thereby increasing the success of clinical studies.